Dichromatic Colour Vision in Wallabies as Characterised by Three Behavioural Paradigms - Ebeling, Wiebke; Hemmi, J. (Public Library of Science, 2014)
Despite lacking genetic evidence of a third cone opsin in the retina of any Australian marsupial, most species tested so far appear to be trichromatic. In the light of this, we have re-examined colour vision of the tammar wallaby which had previously been identified as a dichromat. Three different psychophysical tests, based on an operant conditioning paradigm, were used to confirm that colour perception in the wallaby can be predicted and conclusively explained by the existence of only two cone types. Firstly, colour-mixing experiments revealed a Confusion Point between the three primary colours of a LCD monitor that can be predicted by the cone excitation ratio of the short- and middle-wavelength sensitive cones. Secondly, the wavelength discrimination ability in the wallaby, when tested with monochromatic stimuli, was found to be limited to a narrow range between 440 nm and 500 nm. Lastly, an experiment designed to test the wallaby’s ability to discriminate monochromatic lights from a white light provided clear evidence for a Neutral Point around 485 nm where discrimination consistently failed. Relative colour discrimination seemed clearly preferred but it was possible to train a wallaby to perform absolute colour discriminations. The results confirm the tammar wallaby as a dichromat, and so far the only behaviourally confirmed dichromat among the Australian marsupials.